Effect of Bicarbonate, Iron, and Salt, on Lipid Productivity of Chlorella sp. Extracted by Osmotic Shock Method - Muhamad Maulana Azimatun Nur (Eksergi)
Fossil energy depletion in Indonesia can not be neglected. It is needed renewable energy that environmental friendly and meets demand consumption. One of promising biofuel in Indonesia is biodiesel. However lack of feedstock is main problem due to increasing of customer needs. Chlorella sp. is kind of microalgae that potential for biodiesel source. This research is purposed to optimize influence of bicarbonate, iron, and salt in growth, biomass, and lipid productivity of Chlorella sp. The research was done in 2^3 factorial design in 6 days. Cultivation was maintained in pH 6,2-7,4 and 6000 lux light intensity. Extraction was done by osmotic shock method using wet biomass. Result indicates that addition of bicarbonate and iron give possitive effect on lipid productivity. Addition of salt give possitive effect on biomass and growth rate.